Translator training and professional socialisation. - Way, Catherine; Ruiz Cortés, Elena (Routledge, 2024)
Despite the multiple perspectives on the sociology of translation in this volume, the need to develop analytical tools to understand the mechanisms behind translation as social practice persists, particularly in under-researched areas, such as translator training. Nevertheless, researchers and trainers have pursued avenues of research that have been transformed into innovative training practices and activities. In this chapter, we present several approaches and activities foregrounding how trainee translators can be introduced to professional identity, encouraged to integrate into the profession and professional associations, and also participate in society as active social agents. We consider how professional socialisation can be included in translator training by raising awareness of the translator’s identity both individually and in the eyes of other agents involved in the translation process. This requires trainees to become conscious of the fact that they each belong to a social system and that texts and translation are inevitably produced in social contexts.
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/?srsltid=AfmBOopZcHnD5qpvo_xCpqAYD-O3CMuS46bI9Z6UEXcTyq8iFJzZNVQA
Keywords: Traducción - Estudio y enseñanza; Traducción - Aspectos sociales; Translator training; Professional socialisation; Sociology of translation